Penatalaksanaan Fisioterapi untuk Menurunkan Tekanan Darah pada Lansia yang Mengalami Hipertensi dengan Metode Slow Deep Breathing dan Swedish Massage Therapy di Desa A. Yani Pura - Aniesa Nur Laily Pertiwi; Nafiah Nafiah Nafiah; Yulisha Eva Oktaviani (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2021)
Hypertension is a condition where blood pressure continues to increase in a person who exceeds 120/80 mmHg with a long period of time even though the person is in a state of rest. The purpose of this research is to know physiotherapy management in the elderly who have hypertension and whether decrease in blood pressure after a physiotherapy intervention in the form of slow deep breathing (SDB) and swedish massage therapy (SMT). This study uses case study method using a single sample of hypertensive patients. Treatment is 12 times in 4 weeks time, measured using sphygmomanometer. The results of the research obtained after the evaluation is a decrease in blood pressure in hypertensive conditions. Based on this, SDB and SMT are effectively used in lowering blood pressure in hypertensive conditions. Recommended to future researchers be able to use shorter doses and carry out routine blood pressure checks